Neurovascular Coupling Remains Intact During Incremental Ascent to High Altitude (4240 m) in Acclimatized Healthy Volunteers - Leacy, Jack K.; Zouboules, Shaelynn M.; Mann, Carli R.; Peltonen, Joel D. B.; Saran, Gurkan; Nysten, Cassandra E.; Nysten, Heidi E.; Brutsaert, Tom D.; O’Halloran, Ken D.; Sherpa, Mingma T.; Day, Trevor A. (Frontiers in Physiology, 2018)
Neurovascular coupling (NVC) is the temporal link between neuronal metabolic activity and regional cerebral blood flow (CBF), supporting adequate delivery of nutrients. Exposure to high altitude (HA) imposes several stressors, including hypoxia and hypocapnia, which modulate cerebrovascular tone in an antagonistic fashion. Whether these contrasting stressors and subsequent adaptations affect NVC during incremental ascent to HA is unclear. The aim of this study was to assess whether incremental ascent to HA influences the NVC response. Given that CBF is sensitive to changes in arterial blood gasses, in particular PaCO2, we hypothesized that the vasoconstrictive effect of hypocapnia during ascent would decrease the NVC response. 10 healthy study participants (21.7 ± 1.3 years, 23.57 ± 2.00 kg/m2, mean ± SD) were recruited as part of a research expedition to HA in the Nepal Himalaya. Resting posterior cerebral artery velocity (PCAv), arterial blood gasses (PaO2, SaO2, PaCO2, [HCO3-], base excess and arterial blood pH) and NVC response of the PCA were measured at four pre-determined locations: Calgary/Kathmandu (1045/1400 m, control), Namche (3440 m), Deboche (3820 m) and Pheriche (4240 m). PCAv was measured using transcranial Doppler ultrasound. Arterial blood draws were taken from the radial artery and analyzed using a portable blood gas/electrolyte analyzer. NVC was determined in response to visual stimulation (VS; Strobe light; 6 Hz; 30 s on/off × 3 trials). The NVC response was averaged across three VS trials at each location. PaO2, SaO2, and PaCO2 were each significantly decreased at 3440, 3820, and 4240 m. No significant differences were found for pH at HA (P > 0.05) due to significant reductions in [HCO3-] (P < 0.043). As expected, incremental ascent to HA induced a state of hypoxic hypocapnia, whereas normal arterial pH was maintained due to renal compensation. NVC was quantified as the delta (Δ) PCAv from baseline for mean PCAv, peak PCAv and total area under the curve (ΔPCAv tAUC) during VS. No significant differences were found for Δmean, Δpeak or ΔPCAv tAUC between locations (P > 0.05). NVC remains remarkably intact during incremental ascent to HA in healthy acclimatized individuals. Despite the array of superimposed stressors associated with ascent to HA, CBF and NVC regulation may be preserved coincident with arterial pH maintenance during acclimatization.